Strategy for Business Development of Yogya Kremes Chicken Restaurant in Tulang Bawang District - M. Pindra; Ni Putu Widhia Rahayu (PT FORMOSA CENDEKIA GLOBAL, 2024)
The smallest number of MSMEs in the Tulang Bawang area is 23 and have not experienced any development compared to other districts/cities in Lampung Province. The aim of the research is to analyze business development strategies using SWOT analysis. The research method used in this research is using a qualitative approach with SWOT analysis. The questionnaire will be distributed online with a total of 44 respondents. The results of the research show that the Yogya Tulang Bawang Kremes Chicken Restaurant is in quadrant 1 (Growth) between Strength and Opportunity.